(untitled) (Medicine Today, 2022)
Introduction & Objective: : Low back pain is the commonest cause of activity limitations and absence of work in developing country like Bangladesh. The aim of this study was to chalk out the association between ADL modification with chronic low back pain. Materials & Methods: : This Randomized Clinical Trial was performed in the Department of Physical Medicine and Rehabilitation, JRRMCH, Sylhet. Eighty patients of 30 to 60 years old, fulfilling the selection criteria were included in this study. Patients were divided into two groups after randomization by lottery method. Patients of Group-A were treated with NSAID, Anti-ulcerant & Activity (ADL) Modification while patients of Group-B were treated with NSAID and Anti-ulcerant only. Patients of both groups were treated for six weeks. Main outcome measures were Subjective Pain Intensity Score, VAS, Tenderness Index, Disability due to pain, Spinal Mobility Index and Oswestry Disability Index. Results: Majority of the patients of both groups were 30 to 40 years old (52.5% in Group-A and 47.5% in Group-B). Males were predominant in both groups. While majority belongs to middle socio-economic class, occupationally farmers were majority in both groups (22.5% in Group-A and 20% in Group-B). VAS was better in patients who received instructions about activity (ADL) modification than those who did not receive them. Subjective Pain Intensity Score and Tenderness Index improved in both groups but their difference was not statistically significant. Disability due to Pain and Spinal Mobility Index, both the variables improved at the end of 3rd week and their difference was statistically significant (P<0.05). Conclusion: From the study it can be concluded that Activity (ADL) Modification helps to reduce pain in patients with chronic non-specific low back pain. Medicine Today 2022 Vol.34(2): 140-144